UPAYA YURIDIS MEMPERKECIL DISPARITAS PUTUSAN - Kelly Kelly (Jurnal Hukum Adigama, 2020)
A difference in the imposition of punishment on a decision is something that has happened for a long time, this cannot be eliminated completely. The difference in the imposition of penalties for cases of similar or equal seriousness and then without clear reasons is called disparity. Therefore, the disparity in the judges' decisions can give the convict and the outside community a sense of being unfair. Various kinds of theories about justice from several experts spread in society. Although regarding justice it cannot be answered with the provisions of the measure to determine fair or not, because true justice belongs to God. So that the disparity decision results in an unsatisfactory decision and becomes a relative formula. Until justice is submitted to the judge who is considered to be able to give a decision in accordance with the sense of justice that lives in society. The formulation of the problem is how to reduce the disparity in criminal decisions. The research method used is normative. By using data collection techniques, namely literature study and also conducting interviews. Then the results of this study indicate that the disparity in verdicts cannot be eliminated altogether, but efforts can be made to minimize the disparity in criminal decisions.